New Class of Three-Body States - Guevara, Nicolais L.; Wang, Yujun; Esry, B. D. (My University, 2012)
We calculate the three-body spectrum for identical bosons interacting via attractive 1/r2 potentials. We find an infinite number of three-body states even when the pair interactions are too weak to support any two-body states. These new states thus share this surprising scenario with the Efimov effect, but are not themselves Efimov states. Our effect occurs for both identical bosons and identical fermions, and it persists in the presence of two-body bound states.